Molecular characterization, expression pattern and immunologic function of CD82a in large yellow croaker (Larimichthys crocea) - Liu, Yue; Bai, Yulin; Chen, Sijing; Pu, Fei; Li, Yaxian; Chi, Hongshu; Zheng, Zaiyu; Xu, Peng; Zhou, Tao (Frontiers in Immunology, 2024)
Visceral white spot disease (VWND) caused by Pseudomonas plecoglossicida poses a major threat to the sustainable development of large yellow croaker (Larimichthys crocea) aquaculture. Genome-wide association analysis (GWAS) and RNA-seq research indicated that LcCD82a play an important role in resistance to visceral white spot disease in L. crocea, but the molecular mechanism of LcCD82a response to P. plecoglossicida infection is still unclear. In this study, we cloned and validated the Open Reading Frame (ORF) sequence of LcCD82a and explored the expression profile of LcCD82a in various tissues of L.crocea. In addition, two different transcript variants (LcCD82a-L and LcCD82a-S) of LcCD82a were identified that exhibit alternative splicing patterns after P. plecoglossicida infection, which may be closely related to the immune regulation during pathogenetic process of VWND. In order to explore the function of LcCD82a, we purified the recombinant protein of LcCD82a-L and LcCD82a-S. The bacterial agglutination and apoptosis function analysis showed that LcCD82a may involve in extracellular bacterial recognition, agglutination, and at the same time participate in the process of antigen presentation and induction of cell apoptosis. Collectively, our studies demonstrate that LcCD82a plays a crucial role in regulating apoptosis and antimicrobial immunity.